2015
DOI: 10.11648/j.ajac.20150303.17
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a Polymer of Intrinsic Microporosity (PIM-1) with Penetrants

Abstract: Abstract:The characterisation, solubility testing, and alcohol adsorption studies of PIM-1 are reported. Techniques used for characterisation are N 2 sorption and ATR-FTIR analysis. A number of solvents were tested for their ability to dissolve low molecular weight (~30 000 gmol -1 ), medium molecular weight (~60 000 gmol -1 ), and high molecular weight (~120 000 gmol -1 ) PIM-1.Results showed solubility of PIM-1 in these solvents to be dependent on molar mass. CHCl 3 , tetrahydrofuran (THF), CH 2 Cl 2 , dicho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Consequently, we consider also the value for  of polymer acceptable. The results indicated that both CHCl3 and DCM are good solvents for PIM-EA(H2)-TB (as for PIM-1 [50]), however, the polymer usually shows better interaction with CHCl3.…”
Section: Isotropic Dense Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, we consider also the value for  of polymer acceptable. The results indicated that both CHCl3 and DCM are good solvents for PIM-EA(H2)-TB (as for PIM-1 [50]), however, the polymer usually shows better interaction with CHCl3.…”
Section: Isotropic Dense Filmsmentioning
confidence: 99%
“…In general, the casting solvent also has an important role in determining the free volume morphology of the membrane, exerting a key influence on the gas transport (e.g., sorption, diffusion and permeation) [16]. The solvent properties may influence the final microstructure of a glassy polymer matrix via interaction with the polymer macromolecules, such as dipole-dipole interactions and hydrogen bonding [17][18][19][20]. PIMs, like other highly permeable polymers, tend to retain a considerable amount of casting solvent.…”
Section: Introductionmentioning
confidence: 99%
“…The pore size distributions, shown in Figure C, were calculated using the Horvath‐Kawazoe method, which associates the average interaction energy in the pore to the relative pressure required to fill a specific micropore diameter. From Figure C, it is clear that while all samples show microporosity (pores <20 Å), sample 1 has more of the larger micropores in the pore size distribution with a mean pore size centred at 6.6 Å, similar to the literature for PIM‐1 . With increasing annealing temperature and time, the PIM‐1 samples have a smaller proportion of micropores, suggesting annealing at higher temperature and time enhanced the ultramicroporosity (pores <10 Å).…”
Section: Resultsmentioning
confidence: 99%
“…BET surface areas were calculated by applying the Brunauer Emmett Teller (BET) model within the pressure range recommended by Rouquerol et al . The values shown in Table are in agreement with the literature . The highest apparent BET surface area was obtained for samples 2 and 3.…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that the soaking of microporous polymers in methanol and ethanol can be considered as one of the ways to rejuvenate the polymer permeance [24,25]. The specific interactions of alcohol molecules with polymer chains leads to the enhancement of local segmental mobility of the macromolecules and the most pronounced effect is observed when methanol is used.…”
Section: Fig 3 Sorption Isotherms Of Water Vapor On the Composite Mmentioning
confidence: 99%